El perfil del turista del Cantón Vinces - Pincay Mindiolaza, Odalis Astrid (2022)
The Vinces canton is considered a potential tourist destination for the province of Los Ríos. The purpose of this case study is to define the tourist profile in order to take advantage of the attractions of the canton of Vinces. To speak of the tourist profile is to focus on the identification of a specific tourist demand that visits a destination which shares similar characteristics and qualities. Currently, there is no document that details the segmentation of visitors to the city, which is why this document would be of great help for the creation of projects and programs aimed at these groups. The methodology used in this project includes exploratory, descriptive and mixed research in conjunction with the deductive method. The survey was used as a technique and a questionnaire as an instrument that allowed the collection of precise data from 126 respondents, resulting in the fact that the tourists who come to the Vinces canton the most are groups of young people from the Babahoyo canton.